AGIHO guideline on evidence-based management of COVID-19 in cancer patients: 2022 update on vaccination, pharmacological prophylaxis and therapy in light of the omicron variants - Giesen, Nicola; Busch, Elena; Schalk, Enrico; Beutel, Gernot; Rüthrich, Maria Madeleine; Hentrich, Marcus; Hertenstein, Bernd; Hirsch, Hans H.; Karthaus, Meinolf; Khodamoradi, Yascha; Köhler, Philipp; Krüger, William H.; et al. (European journal of cancer, 2023)
The novel coronavirus SARS-CoV-2 and the associated infectious disease COVID-19 pose a significant challenge to healthcare systems worldwide. Patients with cancer have been identified as a high-risk population for severe infections, rendering prophylaxis and treatment strategies for these patients particularly important. Rapidly evolving clinical research, resulting in the recent advent of various vaccines and therapeutic agents against COVID-19, offers new options to improve care and protection of cancer patients. However, ongoing epidemiological changes and rise of new virus variants require repeated revisions and adaptations of prophylaxis and treatment strategies to meet these new challenges. Therefore, this guideline provides an update on evidence-based recommendations with regard to vaccination, pharmacological prophylaxis and treatment of COVID-19 in cancer patients in light of the currently dominant omicron variants. It was developed by an expert panel of the Infectious Diseases Working Party (AGIHO) of the German Society for Hematology and Medical Oncology (DGHO) based on a critical review of the most recent available data.
Online verfügbar 10. Dezember 2022, Artikelversion März 2023
Gesehen am 06.04.2023